The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s11060-015-1821-2
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with high-grade gliomas: a quantitative longitudinal study

Abstract: The diagnosis of a high-grade glioma usual is followed by functional impairment(s), cognitive decline and an impaired psycho-social well-being. This might well have a significant and negative impact on the health related quality of life. The purpose of this study was to explore physical activity levels, prevalence and severity of anxiety and depressive symptoms and health-related quality of life among patients with a highgrade glioma. This paper is based on a longitudinal mixed methods study. Patients (n = 30)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 71 publications
5
48
0
Order By: Relevance
“…We also found that 22% of patients had a pathological score regarding depression in concurrence with other studies (e.g. [ 6 ]). Depression scores positively correlated with the functional status measured by the KPS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that 22% of patients had a pathological score regarding depression in concurrence with other studies (e.g. [ 6 ]). Depression scores positively correlated with the functional status measured by the KPS.…”
Section: Discussionsupporting
confidence: 92%
“…A number of well-validated and reliable QoL instruments have been standardised, with both general measures and specific modules for various tumour sites, treatment modalities, and additional dimensions like spirituality [ 4 ] (Gill & Feinstein, 1994). However, a combination of a quantitative and qualitative approach may provide a more comprehensive picture of a patient’s QoL [ 5 , 6 ] (Lucchiari, Botturi, Masiero, Pravettoni, 2015; Piil et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the sequence and the nature of the information provided varied, and this difference may partially explain the discrepancies between patients and caregivers as it relates to daily life consequences. Given that previous studies did not retrieve these discrepancies [13,28], longitudinal approaches will determine whether the observed discrepancy diminishes during later stages of the disease [8]. Scores ranging 0-100, the higher the score the higher coping strategy is used *p < 0.05 before correction for multiple testing; **p < 0.01 before correction for multiple testing; ( * ) p < 0.05 after correction for multiple testing correlated with the use of social support by the patient, indicating that the caregiver feels badly when the patient finds external resources but feels valued when the patient does not utilize external support.…”
Section: Discussionmentioning
confidence: 92%
“…The announcement of such a diagnosis and poor prognosis, the effects of the tumor on cognition and functionality, and the toxicity of treatments have rapid and important consequences on the everyday life of patients and their relatives [2,3]. These social, emotional, psychological and physical consequences have already been described [4][5][6], indicating an important quality of life (QoL) alteration at a level that is not normally observed in other cancers [7][8][9][10][11][12][13]. Due to these major lifestyle disruptions, there is an interest in studying how patients and caregivers handle the problems of daily life and how the Abstract Patients with high-grade gliomas (HGG) and their caregivers have to confront a very aggressive disease that produces major lifestyle disruptions.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous longitudinal qualitative study we interviewed patients with HGG and their caregivers, and identified a need for information and guidance regarding symptoms and supportive care interventions . In the same population we quantitatively measured HRQOL over time and found high levels of anxiety among the newly diagnosed patients (Piil, Jakobsen, Christensen, Juhler, & Jarden, 2015).…”
Section: Introductionmentioning
confidence: 99%